Spatial prediction of the risk of exposure to Echinococcus spp. among schoolchildren and dogs in Ningxia Hui Autonomous Region, People’s Republic of China - Cadavid Restrepo, Angela M.; Yang, Yu Rong; McManus, Donald P.; Gray, Darren J.; Barnes, Tamsin S.; Williams, Gail M.; Soares Magalhães, Ricardo J.; Clements, Archie C.A. (Geospatial health, 2018)
The geographical distribution of Echinococcus spp. infections in Ningxia Hui Autonomous Region (NHAR) has been reported to be expanding in response to environmental change. The aim of the present study was to predict and compare the spatial distribution of human seropositivity for Echinococcus granulosus and Echinococcus multilocularis and infections with these parasites in dogs in four counties in the south of NHAR to identify communities where targeted prevention and control efforts are required. Predicted seroprevalence of E. granulosus in schoolchildren and E. granulosus infections in dogs concurred spatially, whereas predicted seroprevalence of E. multilocularis in schoolchildren and E. multilocularis infections in dogs differed spatially. Enhanced vegetation index was significantly associated with E. multilocularis seropositivity among schoolchildren, and infections with E. granulosus and E. multilocularis in dogs. A positive association was also found between dog infection with E. granulosus and cultivated land, and a negative association between human seropositivity for E. granulosus and bare-land/artificial surfaces. The findings of this study support the importance of land cover and climatic variables in determining habitat suitability for Echinococcus spp. infections, and suggest that definitive hosts other than dogs (e.g. foxes) are important in defining the geographical risk of human seropositivity for E. multilocularis in NHAR.